Teknologi Daur Ulang Limbah Tekstil Padat yang Dikoleksi dari Tempat Pembuangan Akhir (TPA) Gampong Jawa Banda Aceh - Novita Novita (Universitas Islam Negeri Ar-Raniry, 2016)
The purpose of this study was to recycle a number of textiles solid wastes into a variety of handycrafts. Material of this research were collected from from landfill at Gampong Java in Banda Aceh. A number of selected textile wasteconverted into benefical products by adopted Patchwork technigues at Department of Education and Family Walfare, Faculty of Teacher Training and Education, Syiah Kuala University. Accuracy for selecting and designing are the most determine aspects for better quality of the products. This recycling program not only reduced environmental pollution by textile solid waste but also and increase incomes of the society as well.